S33 The effects of a novel poly(epsilon-caprolactone) nanocapsule containing the pesticide atrazine on human alveolar epithelium. (December 2018) - Moore, AJS; Dean, LSN; Fraceto, LF; Lima, R; Tetley, TD
Abstract : Background: Atrazine (ATZ; 6-chloro-N2-ethyl-N4-isopropyl-1, 3, 5-triazine-2, 4-diamine), a commonly used herbicide, is potentially harmful to animals and humans. Nanoencapsulation of ATZ within non-toxic, biodegradable poly(epsilon-caprolactone) (PCL) improves ATZ's herbicidal activity 10-fold and reduces environmental persistence. These compounds can reach pulmonary alveoli following inhalation and may be toxic. Hypothesis: Encapsulation of ATZ (NC-ATZ) subdues epithelial toxicity exhibited by ATZ alone. Objectives: To compare cytotoxicity, bioreactivity and uptake of PCL nanocapsules (NC, control), ATZ and NC-ATZ in a human alveolar type 1 epithelial cell model (TT1 cells). Methods: The concentration-dependent effect of NC-ATZ was compared to ATZ and NC alone, focusing on TT1 cell viability (MTT assay), LDH release (LDH assay), reactive oxygen species (ROS) production (DHE and H2DCFDA assays) and inflammatory cytokine release (ELISAs); nanoparticle-TT1 cell interactions were visualised using fluorescently tagged particles (confocal microscopy). Results: Nanoencapsulation of ATZ (NC-ATZ) prevented cytotoxicity seen at 10 ug/ml ATZ (˜75% at 24 hour, ***p<0.001;˜85% at 48 hour, **p<0.01). However, NC-ATZ caused effects not observed with ATZ or NC alone. NC-ATZ significantly increased LDH release at >1 mg/ml after 48 hours, peaking at 5 µg/ml (to >3.5 fold that of unexposed control, **p<0.01).>1 mg/ml NC-ATZ was pro-inflammatory, causing greatest mediator release at 48 hours (5 mg/ml peak: IL-6 ˜100 pg/ml; IL-8 ˜46.3 pg/ml) compared to 24 hours (5 mg/ml peak: IL-6 ˜9.4 pg/ml; IL-8 ˜5.45 pg/ml; **p<0.01). Reactive oxygen species generation was unaffected. Confocal microscopy of fluorescent ATZ and NC-ATZ demonstrated cytoplasmic nanoparticle pan-staining, co-localisation in Golgi, suggesting nanoparticle recycling within 24 hours. Conclusion: Although less overtly cytotoxic, NC-ATZ stimulated significantly more cell membrane damage and inflammatory mediator release than ATZ or NC alone, implying ATZ nanoencapsulation alters bioreactivity. The mechanisms require further investigation to optimise safety/use of the nanopesticide construct and exposure thresholds. Furthermore, it is important to establish possible bioreactivity and toxicity with other lung cells (e.g. AT2 cells and macrophages) and other exposed systems (e.g. dermal and gastrointestinal). Acknowledgments: Dean LSN is part funded by National Institute for Health Research Health Protection Research Unit in Health Impact of Environmental Hazards at Imperial College London in partnership with King's College London and Public Health England. Fraceto LF and Lima R would like to thank São Paulo Science Foundation (Spring 16/50003–4).